Evaluation Of The Application Of Payroll Accounting Information Systems In The Order Of Supporting Internal Control In PT. Sinar Galesong Prima Manado - Deysy Rarung; Jantje Tinangon; Anneke Wangkar (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
Accounting information system is one system that is very important for the company. The payroll accounting information system in each company has been designed very well to facilitate the leadership in making decisions. PT. Sinar Galesong Prima Manado is a company engaged in services and trade that sells goods in the form of cars, spare parts and provides service. This study has a purpose to find out how the application of payroll accounting information systemsin order to support internal control at PT. Sinar Galesong Prima Manado. This study uses a qualitative descriptive method using interviews and documentation. The results of this study explain that the payroll accounting system to improve internal control at PT. Sinar Galesong Prima Manado is quite adequate but there are still some shortcomings in the application of payroll SIA in supporting internal control because there are documents, functions and procedures that have not been implemented by PT. Sinar Galesong Prima Manado. It would be a good idea for the company to improve its structure and carry out a strict separation of functions and record attendance using fingerprints again so that attendance records can be monitored properly sothat the company's operational activitiescan take place in accordance with company goals